Influence of Work Environment Noise to Productivity of Employee Performance of Sidoarjo District - Cahyani, Agustina Astri (Universitas Muhammadiyah Gresik, 2020)
Employees of the Sidoarjo Regency Health Office have a great responsibility in developing and improving health, especially in Sidoarjo Regency but the location of the Sidoarjo Regency Health Office is less strategic because it is located in the center of the traffic crowd which has an impact on employee performance. This study aims to analyze the noise of the work environment on the productivity of the performance of the employees of the Sidoarjo Regency Health Office. This research was observational analytic type. The sampling technique in this study used total sampling, as many as 30 people. The instruments of this research were questionnaire and sound level meter. Data analysis techniques include editing, coding, data entry, and conducting univariate and bivariate analysis techniques.The results of this study are: the majority of Sidoarjo Health Office employees experience high noise with an average noise intensity of 71.01 dBA; most employees of the Sidoarjo Health Office (56.7%) had good work productivity; and there is an influence of environmental noise on employee performance productivity Sidoarjo Health Office with a pvalue of 0.020 <0.05. To improve employee productivity, employees of the Sidoarjo Health Office are expected to submit noise complaints to the leaders of the Sidoarjo Health Office so that they can be addressed immediately and arrange sitting positions while working away from sources of noise and the Health Office is expected to be able to monitor the noise levels of the workspace of employees and immediately make efforts to reduce employee room noise.